Analogia i canvi morfològic: a propòsit de les formes verbals velaritzades - Pérez Saldanya, Manuel (Caplletra. Revista Internacional de Filologia, 1995)
An important series of verbs of the second conjugation exists in Catalan, characterized by a velar obstruent between the radical and the inflectional affixes. This velar segment, which in modern Catalan acts as an extension of the radical, has a heterogeneous historical origin. In short, in certain cases it stems from the strengthening of the glide of the Latin strong perfects in -UI (where w > gw > g); in others, it is justified by the maintaining of the final consonant of the radical in certain forms of the present in verbs such as dico or stringere (DICO > dic, DICAM > diga ...); in others, finally, it is due to changes of a purely analogical nature. In order to explain the latter changes, the theoretical framework of Natural Morphology has been adopted, and the analogical processes are considered to be motivated by a set of principles of morphological naturalness or optimization. To be exact, the inflectional class stability principle, the system congruity principle, the uniformity and transparency principle, and the constructional iconicity principle.